2020
DOI: 10.1177/0194599820938654
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Pepsin Expression and Dysplasia Grade in Patients With Vocal Cord Leukoplakia

Abstract: Objective To measure pepsin expression in patients with vocal fold leukoplakia and elucidate its clinical significance. Study Design Retrospective analysis of pathologic archive specimens. Setting Affiliated university hospital. Subjects and Methods The study included 45 patients with vocal fold leukoplakia and 19 with vocal fold polyps who underwent surgical treatment between December 2013 and July 2016. Masses were detected on both vocal cords in 5 patients with vocal fold leukoplakia and in 1 patient with v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 42 publications
1
22
1
Order By: Relevance
“…Tissue damage caused by pepsin is an important pathogenetic factor [4]. Esophageal mucosal epithelial injury is caused principally by gastric acid secreted by the proton pump H + /K + -ATPase [3]; pepsin damages the laryngopharyngeal epithelium [4,5]. Pepsin is abnormally expressed in patients with voice disorders, vocal cord polyps, laryngeal stenosis, vocal cord leukoplakia, and malignant lesions [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tissue damage caused by pepsin is an important pathogenetic factor [4]. Esophageal mucosal epithelial injury is caused principally by gastric acid secreted by the proton pump H + /K + -ATPase [3]; pepsin damages the laryngopharyngeal epithelium [4,5]. Pepsin is abnormally expressed in patients with voice disorders, vocal cord polyps, laryngeal stenosis, vocal cord leukoplakia, and malignant lesions [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal mucosal epithelial injury is caused principally by gastric acid secreted by the proton pump H + /K + -ATPase [3]; pepsin damages the laryngopharyngeal epithelium [4,5]. Pepsin is abnormally expressed in patients with voice disorders, vocal cord polyps, laryngeal stenosis, vocal cord leukoplakia, and malignant lesions [5,6]. We earlier reported high pepsin levels in vocal cord polyps and patients with vocal cord leukoplakia [5]; the latter expression level increased significantly as the dysplasia grade rose [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that the pepsin level was elevated in vocal cord polyps and leukoplakia and was correlated with the grade of dysplasia [22]. Here, we assessed the effects of acidic pepsin on the growth and viability of laryngeal epithelial cells and found that at low (pH = 3) and moderate (pH = 5) pH, increasing pepsin levels signi cantly increased cell viability (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…Non-acidic pepsin (pH = 7) has been shown to increase the proliferation of laryngeal carcinoma cells [21]. We previously showed that the pepsin level was elevated in vocal cord polyps and leukoplakia and was correlated with the grade of dysplasia [22]. Here, we assessed the effects of acidic pepsin on the growth and viability of laryngeal epithelial cells and found that at low (pH = 3) and moderate (pH = 5) pH, increasing pepsin levels signi cantly increased cell viability (Fig.…”
Section: Acidi Ed Pepsin Enhances Laryngeal Epithelial Cell Growth In Vitro and In Vivomentioning
confidence: 99%